Clinical indications for coronary artery calcium scoring in asymptomatic patients: Expert consensus statement from the Society of Cardiovascular Computed Tomography - Hecht, Harvey; Blaha, Michael J.; Berman, Daniel S.; Nasir, Khurram; Budoff, Matthew; Leipsic, Jonathon; Blankstein, Ron; Narula, Jagat; Rumberger, John; Shaw, Leslee J. (Journal of cardiovascular computed tomography, 2017)
This expert consensus statement summarizes the available data regarding the prognostic value of CAC in the asymptomatic population and its ability to refine individual risk prediction, addresses the limitations identified in the current traditional risk factor-based treatment strategies recommended by the 2013 ACC/AHA Prevention guidelines including use of the Pooled Cohort Equations (PCE), and the US Preventive Services Task Force (USPSTF) Recommendation Statement for Statin Use for the Primary Prevention of Cardiovascular Disease in Adults. It provides CAC based treatment recommendations both within the context of the shared decision making model espoused by the 2013 ACC/AHA Prevention guidelines and independent of these guidelines.